2015
DOI: 10.1515/ijcre-2014-0131
|View full text |Cite
|
Sign up to set email alerts
|

CO2 Sorption-Enhanced Processes by Hydrotalcite-Like Compounds at Different Temperature Levels

Abstract: The aim of this work is to identify solid sorbents for CO 2 capture for coal and biomass syngas conditioning and cleaning by means of a sorption-enhanced reaction process. Hydrotalcite-like compounds (HTlcs) were synthesized with and without K 2 CO 3 impregnation. Samples were characterized by scanning electron microscopy with energy dispersive X-ray spectroscopy (SEM-EDX), X-ray diffraction (XRD), Brunauer-Emmett-Teller (BET) and Barrett-Joyner-Halenda (BJH) porosimetry after synthesis and after capture tests… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

1
2
0

Year Published

2015
2015
2016
2016

Publication Types

Select...
2

Relationship

0
2

Authors

Journals

citations
Cited by 2 publications
(3 citation statements)
references
References 15 publications
1
2
0
Order By: Relevance
“…This consideration is corroborated by Gallucci et al where tests in fluidized bed under TSA conditions have been made on the sorbents thermally treated at T ¼ 700°C [20].…”
Section: Capture Testssupporting
confidence: 54%
See 2 more Smart Citations
“…This consideration is corroborated by Gallucci et al where tests in fluidized bed under TSA conditions have been made on the sorbents thermally treated at T ¼ 700°C [20].…”
Section: Capture Testssupporting
confidence: 54%
“…Dry capture tests indicated that sorption capacity of sorbents increases of 30% with respect to atmospheric pressure results obtained by Gallucci et al [20]. The best sorbent considering the first cycle capacity in the dry tests is HT1-700 (1.60 mmol CO2 /g sorbent ).…”
Section: Discussionmentioning
confidence: 60%
See 1 more Smart Citation